Graduate Employability and Internationalization of the Curriculum at Home - Jones, Elspeth (International Higher Education, 2014)
Employers often complain that university graduates are not equipped with the ‘soft’ employability skills required for today’s global workforce. Education abroad has been shown to develop these skills but this is little understood by institutions or employers. Can the benefits of education abroad be extended to all students through internationalization of the curriculum at home? The author calls for more evidence that such an approach can be effective.